EXPLORING THE UNDERLYING ATTITUDES OF CHEMISTRY UNDERGRADUATES TOWARD ENGLISH FOR ACADEMIC PURPOSES AT UIN JAKARTA - Azramedia Indonesia (Jurnal Multidisipliner Bharasumba, 2026)
This study explores the attitudes of Chemistry students at UIN Jakarta toward the use of English for Academic Purposes. This research used a quantitative approach. Data were collected through a questionnaire distributed to forty-seven Chemistry students at UIN Jakarta. Students’ attitudes were analyzed through three components: cognitive, affective, and behavioral. These components describe what students think about English, how they feel about it, and how they use it in their academic activities. The results show that most students have positive attitudes toward English for Academic Purposes and believe that it helps them improve their academic reading and writing skills. However, many students still experience difficulties, particularly in using academic vocabulary, applying correct grammar, and writing scientific papers related to Chemistry. Students’ attitudes toward English for Academic Purposes are influenced by several factors, such as their previous learning experiences, level of self-confidence, and learning habits. Based on these findings, this study suggests that English for Academic Purposes courses should be more closely related to the students’ field of study and provide additional language support when needed.